Complications of Female Incontinence and Pelvic Reconstructive Surgery - Goldman, Howard B.; Goldman, Howard B. (Current Clinical Urology, 2013)
Complications of Female Incontinence and Pelvic Reconstructive Surgery reviews the prevention, evaluation and management of complications arising from female pelvic surgery. Potential complications of both routine and specialized female pelvic procedures such as transvaginal slings, cystocele and rectocele repairs, urethral diverticulectomy, and transvaginal mesh repairs are reviewed. The chapters are divided by procedure allowing the reader to easily find what they are looking for. Images and figures of methods of evaluation and repair of these complications are included throughout. The volume is organized based on the specific types of surgeries performed and the user is able to look up the type of surgery performed and immediately find all of the potential complications and their treatments. This text will serve as a comprehensive guide and reference allowing the surgeon quick and ready access to information about the complications of female pelvic surgery.